เกณฑ์การจัดสรรนํ้าที่เหมาะสม โดยวิธีหาค่าที่เหมาะสมที่สุดด้วยเทคนิค วิธีอาณาจักรผึ้ง Optimal Water Allocation Criteria using Artificial Bee Colony - กาสีใส, ตระการ; แข็งแรง, อนงค์ฤทธ์ิ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
บทคัดย่อ การวิจัยครั้งนี้มีความมุ่งหมายเพื่อประยุกต์ใช้วิธีหาค่าที่เหมาะสมที่สุดด้วยเทคนิควิธีการอาณาจักรผึ้ง รว่ มกับแบบจำลองการเลียนแบบเพื่อปรับปรุงโคง้ ควบคุมของอา่ งเก็บน้ำ โดยใชค้ า่ เฉลี่ยของการขาดแคลน น้ำนอ้ ยที่สุด ความถี่ของการขาดแคลนน้ำนอ้ ยที่สุด และปริมาณการขาดแคลนสูงสุดที่นอ้ ยที่สุด เปน็ ฟงั กช์ ัน วัตถุประสงค์ในกระบวนการคน้ หาคำตอบ นอกจากนี้ยังไดสั้งเคราะหข์ อ้ มูลน้ำทา่ รายเดือนที่ไหลเขา้ อา่ งเก็บน้ำ จำนวน 100 ชุด เพื่อใชป้ ระเมินประสิทธิภาพของโคง้ ควบคุมที่ไดจ้ ากแบบจำลอง ซึ่งจะแสดงผลเปน็ สถานการณ์ น้ำขาดแคลนและน้ำไหลลน้ ในรูปแบบความถี่ ชว่ งเวลาของเหตุการณ ์ ปริมาณน้ำเฉลี่ย และปริมาณน้ำสูงสุด การศึกษานี้พิจารณาข้อมูลโค้งควบคุมรายเดือนของอ่างเก็บนํ้าลำปาว จังหวัดกาฬสินธุ์ เป็นกรณีศึกษา ซึ่งประกอบไปด้วยข้อมูลปริมาณนํ้าท่าเฉลี่ยรายเดือนที่ไหลเข้าอ่างเก็บนํ้าตั้งแต่ปี พ.ศ. 2511 - 2557 ความต้องการนํ้าจากอ่างเก็บนํ้า และข้อมูลกายภาพของอ่างเก็บนํ้า ผลการศึกษาพบวา่ เมื่อใชฟ้ งั กช์ ันวัตถุประสงคท์ ั้ง 3 รูปแบบขา้ งตน้ นั้น จะไดโ้ คง้ ควบคุมใหมท่ ี่มีรูปรา่ ง คลา้ ยคลึงกับโคง้ ควบคุมเดิม เมื่อนำโคง้ ใหมท่ ี่หาโดยใชค้ า่ เฉลี่ยของการขาดแคลนน้ำนอ้ ยที่สุดเปน็ ฟงั กช์ ัน วัตถุประสงค์ในกระบวนการคน้ หาคำตอบมาทดสอบและเปรียบเทียบกับโคง้ ควบคุมเดิมที่ใชอ้ ยูพ่ บวา่ สามารถ บรรเทาสภาวะนํ้าท่วมและนํ้าขาดแคลนได้ดีกว่าโค้งที่เกิดจากการใช้ฟังก์ชันวัตถุประสงค์อื่นและยังดีกว่า โคง้ ควบคุมเดิมดว้ ย จากนั้นเมื่อนำมาทดสอบและเปรียบเทียบกับโคง้ ควบคุมเดิมเพิ่มเติมอีก โดยการเพิ่ม การใชน้ ้ำชลประทาน 20% และเพิ่มปริมาณฝนใชก้ าร 20% และใชข้ อ้ มูลการไหลเขา้ สูอ่ า่ งเก็บน้ำที่สังเคราะห์ ในอดีตจำนวน 47 ปี 100 ชุดข้อมูล พบว่าก็ยังดีกว่าโค้งควบคุมเดิมอีกด้วย Abstract This research aims to apply the Artificial Bee Colony technique connected with a simulation model in order to improve rule curve of the reservoir. The minimal average water shortage, minimal frequency of water shortages and minimal amount of water shortage were used to be the objective functions for searching procedure. In addition, 100 samples of generated inflow data were used to evaluate the performance of the new obtained rule curves. The results were presented situation of water shortage and excess release in term of frequency and duration, amount of average and maximum. Monthly rule curves of Lampao reservoir located in Kalasin province were considered in this study The inflow record from 1968 to 2014, net water demand from the reservoir, hydrologic data and physical data of the Lampao reservoir were used in the study. The results found that the proposed model with three objective functions provided the new rule curves. The patterns of these rule curves are similar due to seasonal inflow effect and the same conditions. These obtained rule curves were used to evaluate and compare with the existing rule curves. The results present that the rule curves of using average water shortage as an objective function in searching process were suitable than the other rule curves including the existing rule curves. Then, the obtained rule curves of the proposed model using average water shortage as an objective function were used to evaluate with synthetic inflow 100 samples. There were 3 conditions including normal condition, increasing 20% of water demand and increasing 20% effective rain fall. The results also found that the new rule curves of using average water shortage as an objective function can alleviate situations of water shortage and flood more than the other rule curves as well as existing rule curves.